Melodrama en el Altiplano. Maltrato infantil, minería ilegal y salud mental en tres melodramas puneños - Bustamante Quiroz, Emilio (2016)
It is noticeable that, in regional Peruvian cinematography, the most common genre is melodrama, and that the region that has produced the most melodramas is Puno. The characteristics of this genre are reviewed and three melodramas by Juliaca filmmakers are analyzed: Flaviano Quispe’s El hijo del viento, Percy Pacco’s Amor en las alturas, and Marcados por el destino by Óscar Gonzales Apaza. The way genre conventions have been employed in these films (which has enabled effective communication with the public) is described, as well as the way the current issues in the region are addressed therein.